E-book. Revista de Educação Pública, v. 22, n. 51, set./dez. 2013 (Revista de Educação Pública, 2013)
Revista de Educação Pública - v. 22, n. 51 (set./dez. 2013) Cuiabá,EdUFMT, 2013, 240 p.Anual: 1992-1993. Semestral: 1994-2005. Quadrimestral: 2006-ISSNEletrônico 2238-2097ISSNImpresso 0104-5962